Lightning Safety for Florida Agriculture Workers - Shawn T. Steed; Alicia J. Whidden (EDIS, 2018)
Lightning is a common occurrence in the Sunshine State. In fact, Florida is known as the lightning capital of the U.S. and ranks number one in lightning-caused deaths. As Floridians, we have grown accustomed to living with lightning and are possibly complacent about the destructive force that surrounds us. Lightning causes about $5 billion worth of damage and kills an average of 50 people in the U.S. each year. Although lightning kills only about 10% of people struck, many victims can suffer from physical and mental complications for the rest of their lives. In agriculture especially, as employers and employees we need to have a good working knowledge of lightning, its effects, and how to protect ourselves and others from this potentially life-threatening hazard.